THE SINISTRAL STRIKE SLIP FAULT AS AMPANA BASIN CONTROLLER IN CENTRAL SULAWESI - Saragih, Rahmat Yantono; Haryanto, Iyan; Sukiyah, Emi; Ilmi, Nisa Nurul; Sunardi, Edy (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
The presence of gas seepage born in Tanjungapi precisely in the southwestern part of the basin.This remission is supposed to be formed from main rocks of Mesozoic aged. The condition ofAmpana Basin formation cannot be separated from the effect of the relatively northeast-southeastsinistral strike-slip-fault. Based on the 43 outcrop, the main deformation product was identified asan extensional/hybrid joint with a relatively west-east fault line structure on average shear strain(η) = 58o (+) to (η) = 60o (+) and in form of the relatively northwest-southeast strike-slip-faultstructure line with the range of shear strains value between (η) = 45o (+) to (η) = 54o (+). Thekinematics movement of relatively vertical main stress gives a subsidence impact on the surfaceof Mesozoic-Paleogenic aged rock. The sedimentation process of Neogene-aged clastic, from theBongka Formation, Kingtom Formation, and Lonsio Formation ran fast and make the lowerMesozoic-Paleogene-aged rock being burdened by the upper younger rocks. The tectonicdevelopment in Ampana Basin is recorded in Lonsio Formation, Bongka Formation, and limestonein the form of structural indication and deformation showing the period of Central Miocene toHolocene tectonic with the relatively west-east direction of the main regional stress. Keywords: Ampana basin, deformation, strike slip fault, Sulawesi, Tanjungapi